Host associated genetic divergence and sexual isolation in the grasshopper Hesperotettix viridis (Orthoptera : acrididae) - Grace, Tony (Kansas State University, 2009)
Understanding evolutionary processes that structure genetic variation associated with lineage diversification and speciation is a central problem. Shifts in host plant use by insect herbivores and subsequent divergence in mating signals can lead to sexual isolation, especially when selection for specialization on different hosts restricts gene flow among populations. The grasshopper Hesperotettix viridis (Thomas) is an oligophagous grasshopper feeding on plants primarily in the host plant genera Gutierrezia and Solidago in Kansas. I used mitochondrial and microsatellite genetic markers to evaluate the diversification pattern and underlying evolutionary mechanisms of two putative host races of H. viridis. I also quantified host preferences, the degree of sexual isolation among putative host races and divergence in cuticular attributes to identify the nature and origins of initial barriers that isolated populations in the formative stages of divergence. mtDNA data revealed a star-shaped phylogeny, suggesting isolation in a single refugium ~110,000 years ago based on a molecular clock, followed by rapid population expansion. Microsatellite data reveal significant host-based genetic differentiation and structuring in H. viridis populations in Kansas, including a microsatellite locus under strong divergent selection. Neutral microsatellite loci did not reveal a differentiation pattern specific to host plant use. Significant host-based preferences by individuals that fed on two host plant groups were detected in host paired-feeding preference studies. No-choice mate selection experiments revealed preferences for individuals collected from the same host species independent of location with little mating observed between individuals from different host species. Significant differentiation in color and cuticular composition among different host plant races within the study area was also detected. Correlations between host choice, mate choice and phenotypic divergence were observed and this host associated divergence appears to have a genetic basis. Based on the results of this study, I conclude that divergent selection for host plant use underlies observed sexual isolation among populations in this species. Hesperotettix viridis populations in Kansas that fed on Solidago and Gutierrezia species represent two incipient host races, early stages of diversification that could lead to speciation in insect herbivores.
Keywords: Population Genetics; Speciation; Host Associated Divergence; Sexual Isolation; Hesperotettix viridis; Microsatellites; Biology, Genetics (0369)